Hollow tubular ZnCo-X spinel catalyst for efficiently degrading antibiotics in water body
The preparation of hollow tubular ZnCo-X spinel catalyst by grinding method solves the problem that the improvement of Co3O4 catalytic performance in the prior art is difficult to be applicable to large-scale industrial production, and the efficient degradation of antibiotics in water bodies is achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411680002.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
When the prior art improves the catalytic performance of Co3O4 to degrade antibiotics in water bodies, there are problems such as high raw material cost, complex synthesis process, high energy consumption and large amounts of sewage, which is difficult to be applicable to large-scale industrial production.
Hollow tubular ZnCo-X spinel catalyst was prepared by grinding method, using oxalic acid, Co(NO3)2·6H2O and Zn(NO3)·6H2O as raw materials, and roasted in a muffle furnace at 400 °C for 3 hours to obtain highly efficient antibiotics at 3 hours. A catalyst for degradation capacity.
This catalyst can achieve complete degradation of antibiotics in water in a short time, with a high rate constant, and a simple, fast preparation method, low energy consumption and less environmental pollution, making it suitable for industrial applications.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] A hollow tubular ZnCo-X spinel catalyst for efficient degradation of antibiotics in water. Background Art
[0002] New pollutants mainly include persistent organic pollutants, endocrine disruptors, antibiotics, microplastics, etc. Antibiotics in water bodies are hydrophilic, highly accumulative and stable, which makes them easily accumulate in organisms, causing serious environmental pollution and posing a threat to human health. It is urgent to find safe, effective and economical remediation technologies for antibiotic pollution in environmental water bodies.
[0003] At present, advanced oxidation technologies (AOPs) based on free radical catalytic oxidation mechanisms have attracted wide attention in the remediation of antibiotics in water bodies. •- ) has many advantages: higher redox potential of reactive oxygen species (ROS), wider applicable pH range, better selectivity and effectiveness, and can completely oxidize and degrade antibiotics. In the heterogeneous catalytic activation PMS oxidation reaction system, the catalysts containing Co, Fe, Cu and Mn are studied more, all of which have the ability to activate PMS. As a transition metal oxide, Co3O4 has a unique crystal structure and electronic properties and has been widely used as a catalyst for PMS activation. However, the catalytic performance of Co3O4 still needs to be improved, especially for the degradation of antibiotics in water. Modification of Co3O4 to improve its catalytic performance has become a research hotspot. In order to solve such problems, the catalytic performance of Co3O4 is mainly optimized by doping, morphology control and specific surface area regulation. However, the modification methods for Co3O4 usually have expensive raw material costs, complex synthesis processes, high energy consumption and a large amount of wastewater, which are not suitable for large-scale industrial production.
[0004] In this work, we used a simple, fast, low-energy and low-pollution grinding method to prepare hollow tubular ZnCo-X spinel. The obtained ZnCo-X catalyst has a high antibiotic degradation efficiency and can achieve complete degradation of antibiotic pollutants in water in a relatively short time. Summary of the invention
[0005] The invention uses oxalic acid, Co(NO3)2·6H2O and Zn(NO3)·6H2O (Zn(NO3)·6H2O:Co(NO3)2·6H2O= X:1, X = 0.5, 1, 2, 4) as raw materials, grinds them uniformly and then roasts them in a muffle furnace at 400°C for 3 h to prepare ZnCo-X (X = 0.5, 1, 2, 4) catalytic materials. The invention provides a simple preparation method, a fast preparation process, low energy consumption and less environmental pollution. The prepared hollow tubular ZnCo-X (X = 0.5, 1, 2, 4) has a large specific surface area. It can be used to activate PMS to degrade antibiotics in water, and the catalyst is easy to recover and reuse.
[0006] The present invention discloses an efficient method for synthesizing ZnCo-X composite oxide from oxalic acid, Co(NO3)2·6H2O and Zn(NO3)·6H2O (Co(NO3)2·6H2O:Zn(NO3)·6H2O = 1: X, X = 0.5, 1, 2, 4) by grinding method, and obtains good effect on activating PMS to degrade antibiotics represented by tetracycline. The technical scheme adopted is: by a simple, rapid, low energy consumption and less environmental pollution grinding method, oxalic acid, Co(NO3)2·6H2O and Zn(NO3)·6H2O are put into a mortar and ground, and calcined at 400 °C for 3 h in a muffle furnace to prepare ZnCo-X (X = 0.5, 1, 2, 4) catalytic material. The ZnCo-X (X = 0.5, 1, 2, 4) prepared by grinding has a hollow tubular structure, which can not only expose more active sites, but also accelerate the mass transfer process of reactants on the surface. The composite components of ZnCo-X (X = 0.5, 1, 2, 4) catalytic materials can promote the generation of a large number of non-free radicals ( 1 O2) and free radicals (·OH, SO4 ·- 、O2 - ) to remove antibiotics from water bodies.
[0007] The synthesis steps of the above-mentioned ZnCo-X (X = 0.5, 1, 2, 4) catalytic material are as follows: in a typical synthesis process, 36 mmol oxalic acid, 8 mmol Co(NO3)2·6H2O and Zn(NO3)·6H2O, Co(NO3)2·6H2O : Zn(NO3)·6H2O = 1: X, X = 0.5, 1, 2, 4, are put into a mortar, and the mixture is ground into a paste by a mortar rod. Then, the paste mixture is transferred to a crucible and heated from room temperature to 400 °C in a muffle furnace at 10 °C / min and maintained for 3 h. After cooling, a catalytic material ZnCo-X (X = 0.5, 1, 2, 4) with a hollow tubular structure is obtained.
[0008] Catalyst activated PMS to degrade antibiotics in water: Under the reaction temperature of 25 °C, 0.1 g / L of catalyst was added to a 250 mL beaker containing 100 mL of antibiotic aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, respectively. The solution was filtered using a 0.22 µm microporous membrane and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of antibiotics in the water was determined using a UV-visible spectrophotometer under specific wavelength conditions. When the reaction time was 5 min, 100% degradation of tetracycline in water could be achieved using ZnCo-1 as the catalyst, and the rate constant was as high as 1.217 min -1 .
[0009] The hollow tubular ZnCo-X spinel catalyst for efficiently degrading antibiotics in water is characterized in that: when ZnCo-1 is used as a catalyst, after 5 minutes of reaction, antibiotics such as sulfamethazine, sulfamethoxazole, ciprofloxacin, oxytetracycline hydrochloride and florfenicol in water can be degraded by 100%, 100%, 100%, 100% and 98.6%, respectively, and the rate constants are as high as 1.158 min -1 , 1.136 min -1 , 1.048 min -1 , 1.029 min -1 and 0.954 min -1 , which has broad application prospects in the field of water pollution control.
[0010] The above-mentioned hollow tubular ZnCo-X spinel catalyst for efficiently degrading antibiotics in water bodies is characterized by: compared with the traditional technology for preparing ZnCo-X spinel, the preparation method of the present invention is simple, fast, low in energy consumption and less in environmental pollution, and the obtained ZnCo-X spinel catalyst has a higher catalytic efficiency and has prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 (a) is the SEM image of ZnCo-1 catalyst. Figure 1 (b) is the TEM image of ZnCo-1. Figure 1 (c) HRTEM image of ZnCo-1. Figure 1 (d) is a high-angle annular dark field scanning transmission image (HAADF-STEM). Figure 1 (e) EDS element mapping of ZnCo-1.
[0012] Figure 2 N2 adsorption–desorption isotherms of ZnCo-1 catalyst (inset: pore size distribution).
[0013] Figure 3 These are the XRD spectra of ZnO, Co3O4, ZnCo-0.5, ZnCo-1, ZnCo-2 and ZnCo-4 catalysts.
[0014] Figure 4 These are the FT-IR spectra of ZnO, Co3O4, ZnCo-0.5, ZnCo-1, ZnCo-2 and ZnCo-4 catalysts. DETAILED DESCRIPTION
[0015] The present invention is described in detail below with reference to specific implementation cases.
[0016] Implementation Case 1: Specific preparation steps of ZnCo-X, ZnO and Co3O4 catalytic materials: Synthesis of ZnCo-X: In a typical synthesis process, 36 mmol oxalic acid, 8 mmol Co(NO3)2·6H2O and Zn(NO3)·6H2O, Co(NO3)2·6H2O: Zn(NO3)·6H2O = 1: X, X = 0.5, 1, 2, 4, were placed in a mortar and the mixture was ground into a paste by a mortar rod. Then, the paste mixture was transferred to a crucible and heated from room temperature to 400 °C in a muffle furnace at 10 °C / min and maintained for 3 h. After cooling, a catalytic material ZnCo-X (X = 0.5, 1, 2, 4) with a hollow tubular shape was obtained.
[0017] Synthesis of ZnO: 36 mmol oxalic acid and 12 mmol Zn(NO3)·6H2O were placed in a mortar and the mixture was ground into a paste by a mortar rod. Then, the paste mixture was transferred to a crucible and heated from room temperature to 400 °C in a muffle furnace at 10 °C / min and maintained for 3 h. After cooling, the obtained catalytic material was named ZnO.
[0018] Synthesis of Co3O4: 12 mmol Co(NO3)2·6H2O and 36 mmol oxalic acid were placed in a mortar and the mixture was ground into a paste by a mortar rod. Then, the paste mixture was transferred to a crucible and heated from room temperature to 400 °C in a muffle furnace at 10 °C / min and maintained for 3 h. After cooling, a catalytic material Co3O4 with a hollow tubular shape was obtained.
[0019] After obtaining ZnCo-X (X = 0.5, 1, 2, 4) samples, the structure and morphology of the obtained catalytic materials were characterized by scanning electron microscopy and transmission electron microscopy: Figure 1 (a) is the SEM image of ZnCo-1. Figure 1 (b) is a TEM image of ZnCo-1, which has the basic characteristics of a hollow tubular structure. This shows that grinding is conducive to the formation of a tubular structure, and oxalic acid is used as a pore-forming agent and fuel, and the gas products (CO2, water vapor, etc.) produced by combustion and decomposition are released to form a hollow channel structure. Figure 1 (c) is the HRTEM image of ZnCo-1. It can be seen from the figure that lattice fringes with lattice spacing of 0.242 nm and 0.260 nm appear in the ZnCo-1 image, which belong to the ZnCo2O4 / Co3O4 (311) crystal plane and the ZnO (002) crystal plane, respectively. Figure 1 (d) is the high-angle annular dark field scanning transmission image (HAADF-STEM) of ZnCo-1. Figure 1 (e) EDS element mapping of ZnCo-1. Figure 1 e shows that Co, Zn and O elements are evenly distributed, which may be attributed to the complexation effect of oxalic acid.
[0020] Figure 2 The specific surface area (S BET ) and pore size distribution. Figure 2 The N2 adsorption-desorption isotherm of ZnCo-1 catalytic material is a type IV isotherm, indicating that there are a large number of mesoporous structures on the ZnCo-1 catalytic material. The specific surface area of the ZnCo-1 catalytic material is 47.4 m 2 / g, the average pore diameter is 20.2 nm, and the pore volume is 0.24 cm 3 / g. The large specific surface area and multi-level mesoporous structure of ZnCo-1 catalytic material are conducive to the exposure of active sites, accelerating mass transfer, adsorption and activation of reactants, and thus improving the degradation effect of antibiotics.
[0021] Figure 3 The XRD spectra of Co3O4, ZnO, ZnCo-0.5, ZnCo-1, ZnCo-2 and ZnCo-4 catalytic materials are shown below. Figure 3It can be seen that the XRD pattern of Co3O4 has diffraction peaks at 2θ = 31.3°, 37.0°, 38.7°, 44.9°, 55.7°, 59.5° and 65.5°, which are respectively attributed to the (220), (311), (222), (400), (422), (511) and (440) crystal planes of Co3O4 (JCPDS #42-1467). The XRD pattern of ZnO has diffraction peaks at 2θ = 31.8°, 34.4°, 36.3°, 47.6°, 56.6° and 62.9°, which are respectively attributed to the (100), (002), (101), (102), (110) and (103) crystal planes of ZnO (JCPDS #36-1451). The diffraction peaks of Co3O4 and ZnO were observed in the XRD spectrum of ZnCo-X. Compared with the XRD diffraction peak of ZnO, the peak intensity of the diffraction peak attributed to ZnO in ZnCo-X is significantly reduced, which may be due to the fact that some Zn species may be incorporated into the Co3O4 lattice to replace Co 2+ sites, forming a ZnCo2O4 spinel structure.
[0022] Figure 4 The Fourier transform infrared (FTIR) spectra of Co3O4, ZnO, ZnCo-0.5, ZnCo-1, ZnCo-2 and ZnCo-4 catalyst materials are shown in Figure 1. In the Co3O4 catalyst, the -1 and 579 cm -1 The peaks at 2+ -O and Co 3+ -O stretching vibration peak. At the same time, a peak at 675 cm -1 and 579 cm -1 The peak at 2+ -O / Co 2+ -O and Co 3+ The stretching vibration peak of -O indicates that the ZnCo-X catalyst has a ZnCo2O4 spinel structure.
[0023] Implementation Case 2 (Reaction see Table 1, entry 1) Under the reaction temperature of 25 °C, PMS with a set concentration of 0.2 g / L was added to a 250 mL beaker reactor containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5) to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was measured using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the degradation rate of tetracycline by PMS alone was only 3.3%, indicating that the rate constant of tetracycline degradation by PMS ( k = 0.0237 min -1 ) is very small.
[0024] Implementation case 3 (for reactions, see Table 1, entry 2) Under the reaction temperature of 25 °C, 0.1 g / L of ZnO catalyst was added to a 250 mL beaker containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was determined using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the degradation rate of tetracycline by ZnO catalyst was 47.4%, and the rate constant of tetracycline degradation by ZnO catalytic material was k = 0.387 min -1 .
[0025] Implementation Case 4 (Reactions see Table 1, entry 3) At a reaction temperature of 25 °C, 0.1 g / L of Co3O4 catalyst was added to a 250 mL beaker containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was determined using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the degradation rate of tetracycline by Co3O4 was 23.9%, and the rate constant of the degradation of tetracycline by the Co3O4 catalytic material was k = 0.107 min -1 .
[0026] Implementation Case 5 (Reaction see Table 1, entry 4) Under the reaction temperature of 25 °C, 0.1 g / L of ZnCo-1 catalyst was added to a 250 mL beaker containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was determined using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the degradation rate of tetracycline by ZnCo-1 was 100%, and the rate constant of tetracycline degradation by ZnCo-1 catalytic material was k = 1.217min -1 .
[0027]
[0028] Implementation Case 6 (Reactions see Table 2, entry 1) At a reaction temperature of 25 °C, 0.1 g / L of ZnCo-0.5 catalyst was added to a 250 mL beaker containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was measured using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the degradation rate of tetracycline by ZnCo-1 was 84.3%, and the rate constant of tetracycline degradation by ZnCo-0.5 catalytic material was k =0.719 min -1 .
[0029] Implementation Case 7 (Reactions see Table 2, Item 2) Under the reaction temperature of 25 °C, 0.1 g / L of ZnCo-2 catalyst was added to a 250 mL beaker containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was determined using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the degradation rate of tetracycline by ZnCo-2 was 100%, and the rate constant of tetracycline degradation by ZnCo-2 catalytic material was k = 1.018min -1 .
[0030] Implementation Case 8 (Reactions see Table 2, Item 3) At a reaction temperature of 25 °C, 0.1 g / L of ZnCo-4 catalyst was added to a 250 mL beaker containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was determined using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the degradation rate of tetracycline by ZnCo-4 was 100%, and the rate constant of tetracycline degradation by ZnCo-4 catalyst was k = 0.369 min -1 .
[0031]
[0032] Implementation Case 9 (0.025 g / L ZnCo-1 catalyst) At 25 °C, 0.025 g / L of ZnCo-1 catalyst was added to a 250 mL beaker containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered with a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was measured using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, the degradation rate of tetracycline by ZnCo-1 was found to be 50.6%.
[0033] Case 10 (0.05 g / L ZnCo-1 catalyst) At 25 °C, 0.05 g / L of ZnCo-1 catalyst was added to a 250 mL beaker containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered with a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was measured using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, the degradation rate of tetracycline by ZnCo-1 was found to be 79.2%.
[0034] Case Study 11 (0.075 g / L ZnCo-1 Catalyst) At 25 °C, 0.075 g / L of ZnCo-1 catalyst was added to a 250 mL beaker containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered with a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was measured using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, the degradation rate of tetracycline by ZnCo-1 was found to be 95.7%.
[0035] Case Study 12 (0.125 g / L ZnCo-1 Catalyst) At 25 °C, 0.125 g / L of ZnCo-1 catalyst was added to a 250 mL beaker containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered with a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was measured using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the degradation rate of tetracycline by ZnCo-1 was 100%.
[0036] Implementation Case 13 (for reactions, see Table 3, items 1-5) Under the reaction temperature of 25 °C, 2 mg of tetracycline and 100 mL of deionized water were added to the reactor, and then 0.1 g / L of ZnCo-1 catalyst was added. After stirring for 30 min to reach adsorption equilibrium, PMS with the required concentration of 0.2 g / L was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, respectively, filtered with a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was measured using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the degradation rate of tetracycline by ZnCo-1 was 100%, and Co 2+ The leaching concentration was 0.11 mg / L. When the catalyst was reused for the second time after centrifugation, the degradation rate of tetracycline was 100%, and the degradation rate of Co 2+ The leaching concentration was 0.09 mg / L. When the catalyst was reused for the third time after centrifugation, the degradation rate of tetracycline was 98.7%, and the Co 2+ The leaching concentration was 0.12 mg / L. The degradation rate of tetracycline was 97.6% when the catalyst was reused for the fourth time after centrifugation. 2+ The leaching concentration was 0.08 mg / L. The degradation rate of tetracycline was 95.3% when the catalyst was reused for the fifth time after centrifugation. 2+ The leaching concentration is 0.06 mg / L.
[0037]
[0038] Implementation Case 14 (Reaction see Table 4, Item 1, degradation performance of ZnCo-1 catalyst for sulfadimethazine) At a reaction temperature of 25 °C, 0.1 g / L of ZnCo-1 catalyst was added to a 250 mL beaker containing 100 mL of sulfadimethazine aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of sulfadimethazine was determined using a UV-visible spectrophotometer at a wavelength of 265 nm. When the reaction time was 5 min, it was found that the degradation rate of sulfadimethazine by ZnCo-1 was 100%, and the rate constant of the degradation of sulfadimethazine by ZnCo-1 catalytic material was k= 1.158 min -1 .
[0039] Implementation Case 15 (Reaction see Table 4, Item 2, degradation performance of ZnCo-1 catalyst for sulfamethazine) At a reaction temperature of 25 °C, 0.1 g / L of ZnCo-1 catalyst was added to a 250 mL beaker containing 100 mL of sulfamethazine aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of sulfamethazine was determined using a UV-visible spectrophotometer at a wavelength of 267 nm. When the reaction time was 5 min, it was found that the degradation rate of sulfamethazine by ZnCo-1 was 100%, and the rate constant of the degradation of sulfamethazine by the ZnCo-1 catalytic material was k = 1.136 min -1 .
[0040] Example 16 (Reaction see Table 4, entry 3, degradation performance of ZnCo-1 catalyst for ciprofloxacin) At a reaction temperature of 25 °C, 0.1 g / L of ZnCo-1 catalyst was added to a 250 mL beaker containing 100 mL of ciprofloxacin aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of ciprofloxacin was determined using a UV-visible spectrophotometer at a wavelength of 278 nm. When the reaction time was 5 min, it was found that the degradation rate of ciprofloxacin by ZnCo-1 was 100%, and the rate constant of the degradation of ciprofloxacin by ZnCo-1 catalytic material was k =1.048 min -1 .
[0041] Implementation Case 17 (Reaction see Table 4, Item 4, degradation performance of ZnCo-1 catalyst on oxytetracycline hydrochloride) Under the reaction temperature of 25 °C, 0.1 g / L of ZnCo-1 catalyst was added to a 250 mL beaker containing 100 mL of oxytetracycline hydrochloride aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of oxytetracycline hydrochloride was determined using a UV-visible spectrophotometer at a wavelength of 353 nm. When the reaction time was 5 min, it was found that the degradation rate of oxytetracycline hydrochloride by ZnCo-1 was 100%, and the rate constant of the degradation of oxytetracycline hydrochloride by ZnCo-1 catalytic material was k = 1.029 min -1 .
[0042] Implementation Case 18 (Reaction see Table 4, Item 5, degradation performance of florfenicol by ZnCo-1 catalyst) Under the reaction temperature of 25 °C, 0.1 g / L of ZnCo-1 catalyst was added to a 250 mL beaker containing 100 mL of florfenicol aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, respectively, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of florfenicol was determined using a UV-visible spectrophotometer at a wavelength of 266 nm. When the reaction time was 5 min, it was found that the degradation rate of florfenicol by ZnCo-1 was 98.6%, and the rate constant of the degradation of florfenicol by ZnCo-1 catalytic material was k =0.954 min -1 .
[0043]
[0044] Implementation Case 19 (Effect of tert-butyl alcohol quencher on the degradation performance of ZnCo-1 catalyst for tetracycline) At 25 °C, 0.1 g / L ZnCo-1 catalyst and 4 mL methanol were added to a 250 mL beaker containing 100 mL tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, filtered with a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL methanol. After shaking, the concentration of tetracycline was measured using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the addition of tert-butyl alcohol reduced the degradation rate of tetracycline by ZnCo-1 to 45.2%, indicating that hydroxyl radicals (·OH) made a significant contribution to the degradation of tetracycline by ZnCo-1 activating PMS.
[0045] Implementation Case 20 (Effect of methanol quencher on the degradation performance of ZnCo-1 catalyst for tetracycline) At 25 °C, 0.1 g / L ZnCo-1 catalyst and 4 mL methanol were added to a 250 mL beaker containing 100 mL tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, respectively, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was measured using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the degradation rate of tetracycline by ZnCo-1 was 40.8%. The results of the quenching experiments with tert-butyl alcohol and methanol showed that ·OH and SO4 generated in the activation of PMS by ZnCo-1 ·- All contribute to the degradation of tetracycline. ·- In comparison, ·OH made a significant contribution to the degradation of tetracycline by PMS activated by ZnCo-1.
[0046] Case Study 21 (Effect of L-histidine quencher on the degradation performance of ZnCo-1 catalyst for tetracycline) At 25 °C, 0.1 g / L of ZnCo-1 catalyst and 5 mg of L-histidine were added to a 250 mL beaker containing 100 mL of tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, respectively, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was measured using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the addition of L-histidine reduced the degradation rate of tetracycline by ZnCo-1 to 36.1%, which indicates that singlet oxygen ( 1 O2) played a significant role in the degradation of tetracycline by PMS activated by ZnCo-1.
[0047] Implementation Case 22 (Effect of p-benzoquinone quencher on the degradation performance of ZnCo-1 catalyst for tetracycline) Under the reaction temperature of 25 °C, 0.1 g / L ZnCo-1 catalyst and 5 mg p-benzoquinone were added to a 250 mL beaker containing 100 mL tetracycline aqueous solution (20 mg / L, pH=6.5). After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, respectively, filtered using a 0.22 µm microporous membrane, and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of tetracycline was measured using a UV-visible spectrophotometer at a wavelength of 358 nm. When the reaction time was 5 min, it was found that the addition of p-benzoquinone reduced the degradation rate of tetracycline by ZnCo-1 to 89.5%. The results of the quenching experiment of L-histidine and p-benzoquinone showed that in the process of ZnCo-1 activating PMS to degrade tetracycline 1 O2 and O2 - Coexistence, compared to O2 - , generated in the reaction 1 O2 contributes more significantly to the degradation of tetracycline.
Claims
1. A hollow tubular ZnCo-X spinel catalyst for efficient degradation of antibiotics in water, characterized in that: A hollow tubular ZnCo-X spinel catalyst was prepared for the first time by a grinding method with simple preparation steps, rapidity, low energy consumption and less environmental pollution. The preparation steps of the ZnCo-X, X = 0.5, 1, 2, 4, catalyst are as follows: 36 mmol oxalic acid, 8 mmol Co(NO3)2·6H2O and Zn(NO3)·6H2O, Co(NO3)2·6H2O : Zn(NO3)·6H2O = 1 : X, X = 0.5, 1, 2, 4, are put into a mortar, and the mixture is ground into a paste by a mortar rod, and then the paste mixture is transferred to a crucible, and the temperature is increased from room temperature to 400 °C in a muffle furnace at 10 °C / min and maintained for 3 h. After cooling, a catalytic material ZnCo-X having a hollow tubular shape is obtained; The steps of activating PMS to degrade antibiotics in water were as follows: at a reaction temperature of 25 °C, 0.1 g / L of catalyst was added to a 250 mL beaker containing 100 mL of 20 mg / L tetracycline aqueous solution at pH 6.
5. After stirring for 30 min to reach adsorption equilibrium, 0.2 g / L of PMS was added to the beaker to start the degradation reaction. 2 mL of the reaction solution was drawn out with a syringe at 10 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min, respectively. The solution was filtered through a 0.22 µm microporous membrane and injected into a test tube containing 2 mL of methanol. After shaking, the concentration of antibiotics in the water was determined using a UV-visible spectrophotometer under specific wavelength conditions. When the reaction time was 5 min, 100% degradation of tetracycline in water could be achieved using ZnCo-1 as a catalyst, and the rate constant was as high as 1.217 min -1 .
2. The hollow tubular ZnCo-X spinel catalyst for efficiently degrading antibiotics in water according to claim 1, characterized in that: When ZnCo-1 was used as the catalyst, after 5 min of reaction, the degradation rates of sulfamethazine, sulfamethoxazole, ciprofloxacin, oxytetracycline hydrochloride and florfenicol in water were 100%, 100%, 100%, 100% and 98.6%, respectively, with rate constants of 1.158 min. -1 , 1.136 min -1 , 1.048 min -1 , 1.029 min -1 and 0.954 min -1 .
3. The hollow tubular ZnCo-X spinel catalyst for efficiently degrading antibiotics in water according to claim 1, characterized in that: Compared with other methods for preparing ZnCo-X spinel catalysts, the grinding method has the advantages of simple and rapid preparation, low energy consumption and less environmental pollution. The obtained ZnCo-X spinel catalyst has a hollow tubular structure, which can provide better adsorption, activation and mass transfer capabilities for reactant molecules in the activation of PMS to degrade antibiotics, thereby showing excellent catalytic performance, recycling performance and low Co 2+ Leaching.
Citation Information
Patent Citations
Macro preparation method for carbon doped zinc oxide-based visible-light catalyst
CN104148047A
Composite material for restoring polycyclic aromatic hydrocarbon pollution and preparation method and application of composite material
CN108637005A
Preparation method and application of hollow prismatic ferrocobalt oxide heterogeneous Fenton-like catalyst
CN115920899A